Адміністративно-правовий механізм обмеження спільної роботи близьких осіб у системі правосуддя - Польна, О. О. (Ужгородський національний університет, 2022)
Дисертація є комплексним правовим дослідженням, спрямованим на розкриття юридичної сутності адміністративноправового механізму обмеження спільної роботи близьких осіб у системі правосуддя в Україні (далі – АПМОРБО в СП), а також на визначення проблемних питань його функціонування та вироблення конкретних пропозицій щодо вдосконалення правового регулювання цього механізму з урахування досвіду державчленів ЄС. В роботі надано визначення поняттю та розкрито основні ознаки, а також охарактеризовано антикорупційну сутність і значення встановлення адміністративноправового обмеження роботи близьких осіб в системі правосуддя, на підставі чого виокремлено із загальної системи вказаних обмежень адміністративноправовий механізм обмеження роботи близьких осіб у системі правосуддя в Україні. Для усебічного розкриття змісту досліджуваного механізму визначено перелік суб’єктів, форми і методи, основні процедури забезпечення вказаних обмежень у зазначеній системі. Для визначення рівня відповідності сучасного стану функціонування національного адміністративноправового механізму обмеження спільної роботи близьких осіб в системі правосуддя європейським стандартам та вимогам окреслено засади правового регулювання аналогічного механізму в державахчленах ЄС. На підставі аналізу виявлених під час роботи проблем, а також враховуючи вивчений досвід розвинених країн, сформульовано пріоритетні напрями подальшого розвитку правового регулювання АПМОРБО у СП. Вперше розкрито смисл встановлення обмежень для спільної роботи близьких осіб в системі правосуддя, який полягає в тому, що це є необхідна публічноправова заборона, поширена на осіб, котрі реалізували (чи бажають реалізувати) право на доступ до публічної служби в СП, за допомогою якої унеможливлюються кадрові ситуації, що обумовлюють непотизм в СП, який є формою корупції, а опосередковано забезпечується незалежність суду і непорушність режиму функціонування професійної публічної служби в СП. Розвинено концептуальні погляди на антикорупційну сутність і значення АПОРБО в СП, зокрема, антикорупційне значення АПОРБО в СП полягає в тому, що: 1) спільна робота близьких осіб, що перебувають у відносинах підпорядкування, є непотизмом, а тому відповідне обмеження сприяє зниженню динаміки та масштабів поширення корупції в СП; 2) АПОРБО в СП відображає суспільний запит громадянського суспільства щодо справедливого урядування, сприяє авторитету держави, довірі до СП, максимізує позитивні стимули до правомірної поведінки громадян загалом та професійних публічних службовців у СП, зокрема. Удосконалено наукові розуміння та характеристику АПМОРБО в СП, зокрема, встановлено, що для нього характерними є: 1) особливий об’єкт (суспільні відносини з приводу дотримання, забезпечення дотримання, реагування на недотримання зобов’язаними суб’єктами встановленого в законодавстві АПОРБО в СП); 2) мета (створення умов взаємодії суб’єктів, на яких поширено дію АПОРБО в СП, за яких вони розумітимуть свої обов’язки, не порушуватимуть їх, а у разі порушення – зазнають негативних юридичних наслідків) та завдання (ідентифікація ризиків непотизму у процесі здійснення кадрової політики в СП; формування внутрішньо системної політики запобігання порушенням вимог АПОРБО в СП тощо); 3) особливий суб’єктний склад. The thesis is comprehensive legal research aimed at disclosing the juridical essence of the administrative and legal mechanism for restricting the joint activities of closely affiliated persons in the judicial system in Ukraine (hereinafter ALMRACAP in the JS), as well as at identifying problematic issues of its functioning and developing specific proposals for improving the legal regulation of this mechanism considering the EU member states experience. The work gives a definition of the concept and discloses the main features, as well as characterizes the anticorruption nature and significance of establishing administrative and legal restrictions on the work of closely affiliated persons in the judicial system, based on which there have been allocated the administrative legal mechanism of restricting the work of closely affiliated persons in the Ukrainian judicial system. For comprehensive disclosure of the investigated mechanism content, a list of subjects, forms, and methods, basic procedures for ensuring the pointed restrictions in the specified system have been determined. To identify the compliance level of the current state of the national administrative and legal mechanism for restricting the joint activities of closely affiliated persons in the justice system with European standards and requirements, the principles of a similar legal regulation mechanism in the EU member states are outlined. Based on the analysis of the problems identified during the research and considering the experience of developed countries, the priority directions for the further development of the legal regulation of ALMRACAP in the JS have been formulated. For the first time, the meaning of establishing restrictions for the joint activities of closely affiliated persons in the judicial system was revealed, which consists in the fact that it is necessary public law ban, extended to persons who have realized (or wish to exercise) the right to access public service in the JS, with which staffing situations that cause nepotism as a form of corruption in the JS become impossible, as well as indirectly ensures the court independence and the inviolability of the professional public service regime functioning in the JS. Conceptual views on the anticorruption essence and significance of ALMRACAP in the JS have been developed, in particular, the anticorruption value of ALMRACAP in the JS lies in the fact that: 1) the joint activities of closely affiliated persons in subordinate relations are nepotism, and therefore the corresponding restriction helps to reduce the dynamics and scale of the corruption spread in the JS; 2) ALMRACAP in the JS reflects the public demand of civil society for fair governance, promotes the authority of the state, confidence in the JS, maximizes positive incentives for the lawful behavior of citizens in general, and professional public servants in the JS in particular. The scientific understanding and characteristics of ALMRACAP in the JS have been improved, in particular, it has been established that it is characterized by: 1) a special object (public relations regarding compliance, ensuring compliance, responding to noncompliance by obliged entities with the ALMRACAP in the JS established in the legislation); 2) purpose (creation of entities' interactions who are the object to ALMRACAP in the JS, in which they will understand their responsibilities, not violate them, and in case of violation, experience negative legal consequences) and tasks (identifying the risks of nepotism in the process of implementing personnel policy in the JS; forming an internal systemic policy for the prevention of requirements violations at ALMRACAP in the JS, etc.); 3) special composition of entities. The entities’ circle of ensuring compliance with restrictions on joint activities of closely affiliated persons in the justice system in Ukraine has been mainstreamed. The group of such permanent subjects includes 1) a special subject (Council of Judges of Ukraine); 2) subjects of ensuring compliance with ALMRACAP in courts and territorial departments of the State Judicial Administration of Ukraine; the Constitutional Court of Ukraine; in the courts of Ukraine; in the judicial authorities. As separate groups for ensuring compliance with ALMRACAP in the JS, there are: 1) contest entities (competitive commissions for exercising a competition for holding civil service positions of categories “B” and “C” in the courts, bodies and institutions of the JS); 2) nonsystemic entities of ensuring compliance with ALMRACAP in the JS (civil society, mass media). The work further developed a theoretical and practical understanding of the forms, methods and procedures for restricting the common activities of the closely affiliated persons in the JS. In particular, the main forms of such a restriction are 1) legal forms (rulemaking and law enforcement); 2) nonlegal forms (organizational and regulatory, organizational and economic, informational support). It has been substantiated that the main methods of limiting the joint activities of closely affiliated persons in the JS are: 1) conviction of the inadmissibility of closely affiliated persons’ common activities in the JS; 2) encouragement of compliance with ALMRACAP requirements in the JS; 3) enforcement to comply with the requirements of ALMRACAP in the JS; 4) control over compliance with the ALMRACAP requirements in the JS. The procedures are as follows: prevention of these restriction violations (monitoring compliance with the ALMRACAP requirements in the JS; informing about the state of compliance with ALMRACAP requirements in the JS), checking the fulfillment of the ALMRACAP requirements in the JS (checking the fulfillment of the obligation to declare filiations), as well as ensuring the occurrence of legal consequences for violation of this administrative and legal requirement (disciplinary procedures; employee transfer or dismissal). For the first time in the administrative law science, the state of the legal regulation of ALMRACAP in the JS in the EU member states was determined, as a result of which it was established that at the EU level no supranational norms have been created that restrict the joint activities of closely affiliated persons in the professional civil service in general and in the JS in particular. In addition, in a number of the EU member states, the corresponding institution of administrative law is not regulated at all (in particular, in Lithuania, Germany, Portugal, Finland, France, Croatia), and in some countries, this restriction is only partially regulated (in Austria, Belgium). This situation takes place since that, in general, in those states in which there is a low level of tolerance to corruption, there are general rules for preventing conflicts of interest in the public service, the operation of the principles of the rule of law, fairness and transparency of personnel procedures, as well as the activities of public service bodies, that is, traditionally public administration is implemented on real democratic principles. In fact, all this is enough to make nepotism practices impossible. Legislative acts on the judicial system and the status of judges in the EU member states (except Hungary) do not contain normative clauses at all on the inadmissibility of ALMRACAP in the JS and on ways to ensure compliance with the requirements of the corresponding administrativelegal restriction. It was stated that detailing the ALMRACAP requirements is observed in those EU member states, which are characterized by the following facts: 1) the absence of an established tradition of public administration on democratic principles; 2) nepotism as a traditional cultural phenomenon; 3) the level of corruption in recent years begins to show growth dynamics. Therefore, in detail ALMRACAP (and ALMRACAP in the JS) is regulated mainly in those EU member states for which corruption is a serious problem (in Estonia, Poland, Slovakia, and Hungary). Based on theoretical developments, implemented and substantiated in the study, as well as considering the experience of legal regulation in a certain area of the EU developed countries, the current directions of optimizing the administrative and legal mechanism for restricting the common work of closely affiliated persons in the justice system of Ukraine are identified. Taking into account the experience of the EU member states (Estonia, Poland, Slovakia and Hungary), it was proved that it is necessary to create and adopt a draft Law of Ukraine “On strengthening guarantees of restricting the work of closely affiliated persons in the justice system”, which will include persons in familypartnership relations to the list of close persons; outline the provision of ALMRACAP in the JS as a guarantee of ensuring the independence of the courts; determine the deliberate violation by the judge of the ALMRACAP requirements in the JS as a disciplinary offense; define a clear list of positions for which the requirements of ALMRACAP in the JS are extended; consolidate the obligation to inform about the joint activities of closely affiliated persons in the JS; determine the legal consequences of deliberate violation of ALMRACAP in the JS in the form of the onset of disciplinary and administrative responsibility. It has been proven that such changes in legislation would contribute to the optimization of ALMRACAP in the JS if in parallel: 1) the activities of the High Qualification Commission of Judges of Ukraine restored; 2) the Commission on compliance with anticorruption restrictions in the JS was created (a special subject of control over the enforcement of such a restriction); 3) the Unified state register of closely affiliated persons in the JS of Ukraine was developed; 4) jointly with the National School of Judges of Ukraine, training materials and programs were developed to disclose the essence of the ALMRACAP requirements in the JS, the features of preventing violation of the requirements of such a restriction
The administrative and legal mechanism for restricting the joint activities of closely affiliated persons in the judicial system
Keywords: обмеження спільної роботи; близькі особи; система правосуддя; адміністративно-правовий механізм; непотизм; європейська інтеграція; публічно-правові відносини; restriction of joint activities; closely affiliated persons; judicial system; administrative and legal mechanism; nepotism; European integration; public legal relations